A psychobiological framework to the stress-induced overeating - Laborda, Mario A. (Revista de Psicología, 2009)
The Darwinian idea of continuity of the species has justified the research with non-human animals to understand humans. If humans are evolutionarily connected with the rest of the animals, then we can find on them analogous models to study our biology and behavior. In psychology, animal models have demonstrated to be an effective tool for understanding normal and abnormal behaviors. In the present article some examples of animal models in experimental psychopathology are presented, and two illustrative studies of how this type of research can be informative about the etiology, maintenance, and treatment of behavioral disorders are reported.